Self-Presentation of Vanshead Solo's Members as Vans Sneaker Subculture in Instagram Posts - Yusup, Khoiruddin (Universitas Sebelas Maret, 2023)
Vanshead Solo Community, a Vans sneaker enthusiast community that became a place for those who love Vans sneaker that has strong values from skateboarding subculture. Their strong affinity was not only shown in their offline gathering but also in one of the famous online platforms, Instagram. Thus, this research was conducted to find out how its members express and negotiate the values of Vans sneaker in their Instagram accounts as their digital self-representation. This research used digital etnography approach in the collecting and also in the process of analyzing data. In the finding of observation and participation this research used the Greet Hofstede’s Cultural Dimensions theory to see how they negotiated the “Off The Wall” or Vans’ values in their Instagram accounts.This research found that Vanshead Solo members tended to express two values of Vans, Individualism and non-comformity as their self-representation. They developed those values by showing their individual creativity and self-expression. Moreover, this research also found that most of the subjects negotiated Vans values through two cultural dimensions, uncertainty avoidance and individualism by showing lower scores of those values.